TikTok Marketing Communication and Purchase Intention Through Brand Awareness, Brand Engagement, and Perceived Value - Sa’diah , Aulia; Dyah Handayani, Siti (INJECT (Interdisciplinary Journal of Communication), 2026)
The objective of this study is to examine the effect of TikTok social media marketing on purchase intention through the mediating roles of brand awareness, customer brand engagement, and perceived value among consumers of local fashion brands. As digital communication platforms continue to influence consumer behavior, the psychological mechanisms through which social media marketing shapes purchase intention remain insufficiently understood. Using a quantitative approach, data were collected from 200 respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that social media marketing significantly influences purchase intention both directly and indirectly through brand awareness, customer brand engagement, and perceived value. Among the three mediating variables, brand awareness emerged as the strongest mediator, followed by perceived value and customer brand engagement. These findings indicate that TikTok-based communication activities play an important role in helping consumers recognize, remember, and evaluate brands, which subsequently strengthens their purchase intention. This study contributes to digital communication and consumer behavior literature by explaining how social media marketing influences purchase intention through brand awareness, customer brand engagement, and perceived value in the context of Indonesian local fashion brands.